KETAATAN PENGEMUDI DAN PENUMPANG DI JALAN TOL TERHADAP PERATURAN PELARANGAN BERHENTI DI JEMBATAN TOL PADALARANG - Maria Francisca Mulyadi; Mahayoni Mahayoni (Problematika Hukum, 2015)
Regulation aims to provide legal protection to road users performed better highways officers and highway users. Legal awareness highway users should be supported with the empowerment and active community participation. It is necessary to examine the causes in the driver and passenger buses that stop at the edge of the highway, despite being penalized foreclosure license and registration , and legal awareness of the driver and passengers of the bus on the highway and solutions to minimize the infringement on the side of the highway Padalarang in its application. The approach in this study was to specification juridical sociological analytical descriptive and exploratory research. In fact on the highway often stop in violation of the toll road , even for raising and lowering the passenger in highway bridge Padalarang . In addition to the desire of the driver is also influenced many direct requests of the passengers. Regulations on the highway does not apply so as a decoration without function has been lost because of cultural shame in breaking the rules and the loss of a sense of obedience to rules , and do not pay attention to the rights of others in the use of toll roads.